Academic optimism - Gurol, Mehmet; Kerimgil, Seda (Elsevier Science Bv, 2010)
Academic optimism depends on positive psychology whose foundation based on scientific research contributing to the general wellness of the public and struggling to understand the individual traits. The three properties of academic optimism have interacted each other. Academic emphasis, being one of these features, triggers student achievement by carrying students' learning to the top level. Collective efficacy reflects the thoughts and beliefs of the group. By increasing trust in school, student and parent trust increases and this strengthens the trust for school. In conclusion, despite the socio-economic status of the students, the triplet structure of academic optimism affects student achievement in a positive way. (C) 2010 Published by Elsevier Ltd.
1st World Conference on Learning, Teaching and Administration (WCLTA) -- OCT 29-31, 2010 -- Amer Univ, Cairo, EGYPT
Keywords: Academic optimism; academic emphasis; collective efficacy; faculty trust